Inteligencia emocional: la compreensión emocional y las relaciones entre pares en el jardín de infancia - Santos, Natalie de Nóbrega dos (2016)
The main models of emotional intelligence (IE) were design primarily for adults, not for children. For this reason, many aspects of the EI rarely studied in preschoolers. Thus, this study aims to ana lyze the emotional understanding (CE), a complex construct, considered a key component of IE in young children and that includes various skills, including the differentiating one’s emotions and understand the emotions of others based in facial expressions and characteristics of situations of emotional context. Our goal is to analyze the relationship between emotional understanding and peer relations. The sample consisted of 210 children between 3 and 6 years of age, which were adminis tered the Test of Emotion Comprehension (TEC, Pons et al., 2004, translated to Portuguese by Roazzi et al. 2008) and a sociometric test. The results confirm that, increasing the age increases the level of CE and emotional understanding may influence peer relationships.